The Study of Correlation Between Bronchiectasis Severity Index and FACED Score for Assessment of Severity of Bronchiectasis - Prajapati, Palak; Jindal, Savita; Dutt, Nilesh; Kapadia, Vishakha; Tripathi, Sanjay (National Journal of Community Medicine, 2022)
Introduction: Two different validated scores are currently used to assess the severity of bronchiectasis: the FACED score and the Bronchiectasis Severity Index (BSI). The study was conducted to evaluate clinical etiology in bronchiectasis patients. And to compare the results of the assessment of bronchiectasis severity obtained via FACED and BSI scores. Methods: The study was conducted at a tertiary care hospital in the outpatients of the department of respiratory medicine. Detailed clinical history and necessary investigations were done. BSI and the FACED score were calculated. Statistical analysis was performed using the SPSS package. Results: According to the FACED score, we found 28 patients with mild bronchiectasis, 17 with moderate, and 5 with severe bronchiectasis. The frequency of patients with low, intermediate, and high BSI was 24, 21, and 5, respectively. Moreover, we observed a weak but statistically significant association of 43% agreement between FACED and BSI scores: Fisher’s exact test(p=0.399), tau-b de Kendall (-0.123; p = 0.337) and kappa test (0.032; p = 0.878). Conclusions: There is a small but significant correlation between the two scales (BSI and FACED). a tendency is observed for patients to be classified with a higher BSI compared to the FACED score.